Dare you to - McGarry, Katie (Don Mills, Ont. : Harlequin Teen, 2013)
Forced to choose between her mom's freedom and her own happiness, skater girl Beth Risks moves in with an aunt. At her new school friends of Ryan Stone, a popular baseball jock, dare him to ask Beth out on a date. What follows is an intense attraction that neither Ryan nor Beth expected.
Includes playlist and Q&A with Katie McGarry.
Keywords: Teenagers -- Fiction; High schools -- Fiction; Dysfunctional families -- Fiction; Mothers and daughters -- Fiction; Dating (Social customs) -- Fiction; Skateboarders -- Fiction; Baseball players -- Fiction; Love stories